2021
DOI: 10.21037/tgh-20-235
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review of the modern surgical management of pediatric choledochal cysts

Abstract: Choledochal cysts (CC) ae rare congenital dilations of the biliary tract that harbor lifelong malignancy risk. CC are treated with surgical excision and bilioenteric reconstruction. In the modern era, the surgical approach to pediatric patients has enjoyed significant innovation with regards to minimally invasive techniques. In this review, we discuss these advances, including laparoscopic, single-incision laparoscopic, and robotic strategies, with a focus on the clinical outcomes of patients undergoing these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
11
0
2
Order By: Relevance
“…Medical treatment limits to the administration of antimicrobial therapy in case of cholangitis or supportive therapy in pancreatitis, trying to stabilize the patient prior to operative approach. If rupture of the cyst manifests, a drainage must be placed, pointing out the weirdness of these presentation [53].…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical treatment limits to the administration of antimicrobial therapy in case of cholangitis or supportive therapy in pancreatitis, trying to stabilize the patient prior to operative approach. If rupture of the cyst manifests, a drainage must be placed, pointing out the weirdness of these presentation [53].…”
Section: Managementmentioning
confidence: 99%
“…Historically, drainage or cystenterostomy was the surgical management, but the high risk of malignant transformation and the recurrence of the symptoms demands aggressive surgical management as the overriding treatment [53,54].…”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Singleport laparoscopic surgery is a new technique in which the entire procedure is performed through an incision with a single port containing 3 or 4 small ports. The feasibility and safety of single-port laparoscopic CDC excision and Rouxen-Y hepaticoenterostomy (SPCH) have been confirmed in some case series (6)(7)(8)(9), and it has demonstrated cosmetic advantages, the likelihood of less pain, and a shorter recovery period due to the reduction of trocar sites (10). However, SPCH is a technically challenging procedure and requires the surgeon to have abundant experience with the traditional laparoscopic procedure; moreover, single-port operations usually last 30% longer than their traditional laparoscopic counterparts and are more likely to produce incision complications (11).…”
Section: Introductionmentioning
confidence: 98%
“…Type V is treated synonymously with Caroli disease, one of the so-called fibropolycystic diseases, but differs from congenital hepatic fibrosis in the thickness of the bile ducts that are damaged ( 10 , 11 ). Almost 80% of choledochal cysts (CCs) are now discovered prenatally or in infancy ( 12 ), but it has been reported that biliary cirrhosis rapidly progresses from the neonatal period to the infantile period in some cases of CBD ( 13 ). We herein report an infantile case of CBD that showed severe biliary cirrhosis at the diagnosis, which was treated by laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%